Unraveling the role of informal mutual aid networks in maintaining urban farms in Lubumbashi, Democratic Republic of Congo - Kesonga Nsele, Maurice; Dogot, Thomas; Maréchal, Kevin (Frontiers in Sustainable Food Systems, 2023)
Introduction The multiple constraints of urban agriculture have prompted farmers in Lubumbashi to turn to informal mutual aid networks. The survey data collected from 88 farmers chosen at random from the 202 farmers previously interviewed enabled us to decipher the crucial role of mutual aid in maintaining urban farms. Methods The survey data collected from 88 farmers chosen at random from the 202 farmers previously interviewed enabled us to decipher the crucial role of mutual aid in maintaining urban farms. Results The results show that 79.5% of the surveyed farmers resort to mutual aid to ensure the vegetable production cycle. More specifically, this mutual aid consists in sharing resources, for which the farmer would interact 15.1 times with other farmers, and in sharing agricultural know-how, for which the farmer would interact 11.6 times with other farmers. Four categories of resources are defined in this mutual aid network: highly exchanged resources with a high exchange intensity (hoes, watering cans, plant protection products and chicken droppings), highly exchanged resources with a low exchange intensity (land capital, spades, and seeds), lowly exchanged resources with a low exchange intensity (motor pumps and buckets) and non-exchanged resources (financing, labor, chemical fertilizers). Agricultural know-how such as soil preparation, soil fertility management, pest control and sales techniques are widely shared. Characteristics such as gender, age, experience, religious affiliation, and farmer status in the household are statistically significant explanatory factors of mutual aid. In addition, neighborhood relations, kinship and religious affiliation are social ties that enable farmers to help each other. Discussion The results provide useful information on the crucial role played by informal mutual aid networks in maintaining urban farms in the face of the negative consequences of chaotic urbanisation and climate change. The study recommends that policymakers and agricultural extension services take these networks into account when drawing up policies for disseminating innovations. For, although informal, they constitute powerful and inexpensive channels of communication in an inoperative institutional context of urban agriculture.